MENINGKATKAN KEMAMPUAN BERBAHASA INDONESIA SISWA SD LUVETA SURABAYA MELALUI LITERASI BERBASIS MEDIA DIGITAL - Nur Rohmah (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2021)
The purpose of this study was to improve the Indonesian language skills of Luveta Elementary School Surabaya students through digital media-based literacy. This research is a qualitative research. The research subjects were students of SD Luveta Surabaya. Data collection techniques were carried out by means of observation, interviews, and documentation. Based on the results of the study, it was found that digital media-based literacy activities helped students in developing oral and written skills. At the habituation stage is the key to the success of literacy. The average student still has problems because the vocabulary is still lacking so that the ability to compose sentences is still not optimal. However, at the development stage students begin to be able to adapt and be able to understand well the contents of the reading and be able to express opinions with the right diction, the sentence structure still needs to be improved and also needs to practice loading conclusions. While in the third stage of learning, students are getting better because they are able to read with good pronunciation and intonation. Meanwhile, to make student resumes, there are no scores below the average, meaning that the clarity of content, spelling, completeness, wording, and neatness is getting better.